Implementasi Sistem Informasi pada Remaja Masjid (Masjid Al-Adnin Perum Pemda Stabat Langkat) - Erwan Efendi (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2023)
Youth mosque is a forum for collaboration carried out by two or more teenagers who are related to the mosque to achieve common goals. There are several functions of mosque youth, namely to prosper the mosque, support Ta'mir Masjid activities, religious, social and economic da'wah activities, as well as fostering Muslim youth in the neighborhood around the mosque. The activities carried out by the youth of the mosque were able to arouse the enthusiasm of the local residents to continue to revive the mosque while maintaining a sense of solidarity between residents. A web-based information system is a system to facilitate the activities of mosque youth in carrying out da'wah activities or organizations. Where is the current condition of the community undergoing activity restrictions due to the pandemic. Training on Da'wah Information Systems and Web-Based Organizations for youth at Masjid Al- adnin is expected to be an inspiration to use this system for other more useful things, either for learning activities or other educational activities. So that the activities of the youth of the Nurohman mosque are even better and the da'wah that will be carried out can be reached quickly and preciselyThis research method uses field research or observation in the target area of the case study in this article. The purpose of this article was created to study the application of information systems in everyday life which makes youth mosques as an example.